External sources of political connections: financial advisors and Chinese acquisitions - Bi, XiaoGang; Wang, Danni (Wiley, 2018)
This study considers the effects of an external form of political connection, namely, politically connected financial advisors, on the value creation of Chinese acquiring firms over the period 2004–2014. Using data consisting of 1,623 Chinese mergers and acquisitions (M&As) deals, we show that politically connected financial advisors create significantly higher market value for acquiring firms, after controlling for firms' own political connections and reputation. Further analysis indicates that the appointment of political advisers can improve an acquiring firm's long‐term industry‐adjusted operating performance and help acquirers reduce bid premiums. We show that private firms and stock‐pay acquisitions are more likely to appoint politically connected financial advisors in M&A transactions, whereas our findings remain unchanged after controlling for endogeneities.